Rapid Magma Generation or Shared Magmatic Reservoir? Petrology and Geochronology of the Rat Creek and Nelson Mountain Tuffs, CO, USA - Sliwinski, Jakub; Farsky, David; Lipman, Peter W.; Guillong, Marcel; Bachmann, Olivier (Frontiers in Earth Science, 2019)
The San Luis caldera complex in the Southern Rocky Mountain Volcanic Field (CO, USA) consists of three overlapping calderas that overlie the sources of three large-volume mid-Cenozoic ignimbrites: the Rat Creek Tuff (RCT; zoned dacite-rhyolite, 150 km3), the Cebolla Creek Tuff (mafic dacite, 250 km3) and the Nelson Mountain Tuff (NMT; zoned dacite-rhyolite, 500 km3), which are indistinguishable in age by 40Ar/39Ar dating. In this study, we argue for a shared magmatic history for the three units on the basis of mineral trace element compositions (plagioclase, sanidine, biotite, pyroxene, amphibole, titanite and zircon), as well as zircon U-Pb geochronology in the RCT and NMT. It is postulated that these latter two are cogenetic, having occupied an elongated magma reservoir that erupted in two stages, prior to and following the eruption of the Cebolla Creek Tuff. This necessitates large-scale lateral magma transport of the NMT magma, which is corroborated by the formation of the nearby Cochetopa caldera with a paucity of intracaldera eruptive products. The implications of lateral magma transport and evolution in integrated magma chambers are discussed in the context of calculating magma fluxes, which can be redefined as an area-normalized flux to avoid inconsistencies in flux estimations.